Association of signalment parameters with activity of pet dogs*. (25th September 2014) - Michel, Kathryn E.; Brown, Dorothy C.
Abstract: Activity monitors are increasingly being used to quantify the activity of pet dogs. The aim of the present study was to investigate associations between signalment and activity of free-living pet dogs. Healthy pet dogs were recruited to wear an Actical activity monitor on their collars continuously for 2 weeks in their home environment. At least fifteen dogs were enrolled in each of the following weight ranges: <10, 10–20, 21–30, 31–40, >40 kg and their age, sex and reproductive status recorded. Each dog's intensity of activity for each minute of recording was classified using the total counts for that minute and our pre-established cut-points. The percentage of time dogs spent in sedentary, light or moderate/vigorous activity each day was calculated. Median total daily activity counts and median percentages of time dogs spent in activities of differing intensity were used for the analysis. Associations between signalment characteristics and activity parameters were evaluated with the Mann–Whitney test, the Kruskal–Wallis test and Spearman rank correlations. Ninety-eight dogs were enrolled with ≥17 dogs in each weight category. Time that dogs were sedentary correlated positively with age ( r 0·50, uncorrected P < 0·001), while the median total daily activity count ( r −0·47, uncorrected P < 0·001), time spent in light ( r −0·46, uncorrected P < 0·001) and more vigorous activity ( r −0·50, uncorrected P < 0·001) were negatively associated with age. No other significant associations between signalment and activity parameters were found. The lack of differences in activity across weight categories may reflect the impact of lifestyle negating any potential behavioural differences across breeds.